New clinical screening strategy to distinguish HNF1A variant-induced diabetes from young early-onset type 2 diabetes in a Chinese population. Issue 1 (31st March 2020) - Ma, Yumin; Gong, Siqian; Wang, Xirui; Cai, Xiaoling; Xiao, Xinhua; Gu, Weijun; Yang, Jinkui; Zhong, Liyong; Xiao, Jianzhong; Li, Meng; Liu, Wei; Zhang, Simin; et al.
Abstract : Objective: Maturity-onset diabetes of the young caused by hepatocyte nuclear factor-1 alpha ( HNF1A ) variants ( HNF1A -MODY) is a common form of monogenetic diabetes. Although patients with HNF1A -MODY might specifically benefit from sulfonylurea treatment, available methods for screening this specific type of diabetes are not cost-effective. This study was designed to establish an optimized clinical strategy based on multiple biomarkers to distinguish patients with HNF1A -MODY from clinically diagnosed early-onset type 2 diabetes (EOD) for genetic testing in a Chinese population. Research design and methods: A case–control study including 125 non-related young patients with EOD and 15 probands with HNF1A -MODY (cohort 1) was conducted to evaluate reported biomarkers for HNF1A -MODY. A cut-off for the fasting insulin (Fins) level, the 97.5 percentile of 150 healthy subjects with normal components of metabolic syndrome (cohort 2), was used to filter out individuals with obvious insulin resistance (Fins <102 pmol/L). An optimized clinical screening strategy ( HNF1A -CSS) was established, and its effectiveness was assessed in another group of 410 young patients with EOD (cohort 3). Results: In cohort 1, body mass index (BMI), serum high-density lipoprotein cholesterol (HDL-c) and high-sensitivity C reactive protein (hs-CRP) levels were confirmed to be useful for the differential diagnosis of HNF1A- MODY. In cohort 3, eight probands with HNF1A -MODY were identified. In cohort 3 and young relatives with HNF1A -MODY, meeting three of four criteria (BMI <28 kg/m 2, hs-CRP <0.75 mg/L, Fins <102 pmol/L and HDL-c >1.12 mmol/L), the sensitivity and specificity of HNF1A -CSS were 100% and 69.3%, respectively. In the pooled analysis of all young patients, HNF1A -CSS displayed 90.5% sensitivity and 73.6% specificity for identifying patients with HNF1A- MODY among those with clinically diagnosed EOD. Conclusion: Our HNF1A -CSS is useful for distinguishing patients with HNF1A -MODY from patients with EOD in a young Chinese population.